Tatar Philistine Family of Kazan in the Middle of the XIX Century - Bessonova, Tatyana V.; Khanova, Aigul F. (Journal of History Culture and Art Research, 2018)
The article examines the demographic and socio-economic characteristics of the Tatar bourgeois family of Kazan in the middle of the XIX century in the era of transition to bourgeois society. Studying the philistine family allows one to get an idea of the way of life of the townspeople, since philistinism was the most massive layer of the urban population of Russia in this period. Kazan, being a multi-confessional and multinational city, along with Russian residents, included the Tatar population in the urban society. The study of the Tatar philistine family makes it possible to reveal the features of the way of life of this category of urban inhabitants, distinguishing it from the Russian philistines of Kazan. Approaches to the study of this issue are based on methods used in microhistory using historical and demographic analysis tools. The study showed that the Tatar philistine family in its structure, demographic characteristics, occupation, standard of living as a whole led a way of life typical of this class group of Russian society of the period under study. However, petty bourgeois Tatars retained a number of features determined by national traditions.